2019
DOI: 10.3329/bjch.v43i1.41213
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Changes in Children with Acute Lower Respiratory Tract Infection

Abstract: Background: Acute Lower Respiratory Tract Infections (ALRI), particularly Pneumonia and Bronchiolitis, are important causes of death in childhood in Bangladesh. The cardiovascular and respiratory systems function as a single unit and alteration in cardiorespiratory interactions, can cause significant changes in cardiac function. The objective of this study was to find out any electrical and functional changes, myocardial injury, frequency of heart failure and the outcomes in these patients with ALRIs. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In various studies, the incidence of CHF in children with LRTI was reported as 10 to 72%. 7,[19][20][21][22] In the present study, CHF was detected in 10% of patients with LRTI.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…In various studies, the incidence of CHF in children with LRTI was reported as 10 to 72%. 7,[19][20][21][22] In the present study, CHF was detected in 10% of patients with LRTI.…”
Section: Discussionmentioning
confidence: 86%
“…Considering the studies evaluating the prevalence of PH via Doppler echocardiography in children with LRTI, the prevalence of LRTI-associated PH was 33.3% in children with pneumonia and 15% in children with bronchiolitis in a study by Kabir et al, 7 and 24% in 75 infants with acute respiratory disease in a study by Bardi-Peti and Ciofu. 23 Üner et al 24 and Sreeram et al 25 reported prevalence of, respectively, 40.5% in children with pneumonia and 52.38% in children with acute bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The cardiovascular and respiratory systems function as a single unit and alteration in cardiorespiratory interactions can cause significant changes in cardiac function [ 8 ]. Studies in adult patients revealed that the presence of a cardiac event, such as congestive heart failure (CHF), is among the leading complications that increase the chances of morbidity and mortality among patients with LRTI [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%